2019
DOI: 10.1088/2053-1591/ab0a49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strontium on the microstructure and mechanical properties of aluminium ADC12/Nano-SiC composite with Al-5TiB grain refiner by stir casting method

Abstract: The effects of Sr addition on mechanical properties and microstructure of aluminium ADC12/Nano-SiC composites produced by stir casting have been investigated. The addition of Sr into ADC12 matrix was varied from 0.01 to 0.03 wt.% and the other elements added were Al-5TiB as a grain refiner and Mg as a wetting agent. It was found that the phases present in composites analysed by Scanning Electron Microscope link to Energy Dispersive Spectra was Mg2Si primary, Mg2Si binary, β-Al5FeSi and Al2Cu respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The addition of 5% magnesium was derived ADC12 alloy ternary system from Al-Si-Cu into Al-Si-Mg. As a result, the intermetallic compound of Mg 2 Si was emerged and formed in primary, binary, and ternary structure during as cast, as shown in figure 6b-f, which lead to improve mechanical properties [19,22]. This seems to be associated with quasi-binary Al-Mg2Si derived from the Al-Mg-Si ternary diagram [23].…”
Section: Microstructure Analysis Adi Journal On Recent Innovation (Ajri) P-issn : 2685-9106 Vol 3 No 1 September 2021 E-issn : 2686-0384mentioning
confidence: 99%
“…The addition of 5% magnesium was derived ADC12 alloy ternary system from Al-Si-Cu into Al-Si-Mg. As a result, the intermetallic compound of Mg 2 Si was emerged and formed in primary, binary, and ternary structure during as cast, as shown in figure 6b-f, which lead to improve mechanical properties [19,22]. This seems to be associated with quasi-binary Al-Mg2Si derived from the Al-Mg-Si ternary diagram [23].…”
Section: Microstructure Analysis Adi Journal On Recent Innovation (Ajri) P-issn : 2685-9106 Vol 3 No 1 September 2021 E-issn : 2686-0384mentioning
confidence: 99%
“…Zulfia. et al [ 23 ] concluded that Sr content had a negligible impact on the hardness and wear rate of ADC12/0.03% volume fraction (vf) Nano‐SiC.…”
Section: Introductionmentioning
confidence: 99%